Production and purification of avian antibodies (igys) from inclusion bodies of a recombinant protein central in nad+ metabolism (2013)
The use of hens for the production of polyclonal antibodies reduces animal intervention and moreover yields a higher quantity of antibodies than other animal models.  The phylogenetic distance between bird and mammal antigens, often leads to more specific avian antibodies than their mammalian counterparts.Since a large amount of antigen is required for avian antibody production, the use of recombinant proteins for this procedure has been growing faster over the last years. Nevertheless, recombinant protein production through heterologous systems frequently prompts the protein to precipitate, forming insoluble aggregates of limited utility (inclusion bodies). A methodology for the production of avian polyclonal antibodies, using recombinant protein from inclusion bodies is presented in this article.In order to produce the antigen, a recombinant Nicotinamide mononucleotide adenylyltransferase from Giardia intestinalis (His-GiNMNAT) was expressed in Escherichia coli.  The protein was purified through solubilization from inclusion bodies prior to its renaturalization.  Antibodies were purified from egg yolk of immunized hens by water dilution, followed by ammonium sulfate precipitation and thiophilic affinity chromatography.The purified antibodies were tested against His-GiNMNAT protein in Western blot essays. From one egg yolk, 14.4 mg of highly pure IgY were obtained; this antibody was able to detect 15ng of His-GiNMNAT.  IgY specificity was improved by means of antigen affinity purification, allowing its use for parasite protein recognition.